If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -15 = 24 Reorder the terms: -15 + 4x = 24 Solving -15 + 4x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 4x = 24 + 15 Combine like terms: -15 + 15 = 0 0 + 4x = 24 + 15 4x = 24 + 15 Combine like terms: 24 + 15 = 39 4x = 39 Divide each side by '4'. x = 9.75 Simplifying x = 9.75
| 3x^2-x-72=0 | | (3/4)-(1/2)n=(5/8) | | 5(6-4)=u+21 | | 3(x+8)=75 | | 25=5t | | 8=2w | | 2=2(3x+5)-2 | | 2(3x+4)+3=5x+20 | | Y=4cos(2-3x) | | 6p-3=39 | | 2y+5=y | | 14m+5n-6m+8n= | | -1+6p=23 | | 6p-1=23 | | -5x-10=17 | | 100+4x=400 | | 6-3p=42 | | 3(2y+4)=8 | | 3(2x+1)-1=4(x+1) | | y=-4tanx | | 100-20= | | 3x^2-2xy+y^2=6 | | 3(2y-7)=18 | | 15-5q=4 | | x^2+4x-13=-8 | | 2x^3-2x^2-6x=0 | | 5(19.50+-1y)+5y=97.50 | | 4(2-x)-(x-8)=-4 | | X+[X-14]=350 | | 5x+5y=97.50 | | (2x+7)(x^2-9)(2x-5)-91=0 | | 2x+3y=46.50 |